(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Assess nutritional status and some digestive symptoms of cancer patients receiving chemotherapy at Hanoi Medical University Hospital. Research subjects and methods: Descriptive cross-sectional study on 141 cancer patients receiving chemotherapy. Results: The rate of malnutrition in patients receiving chemotherapy according to BMI, PG-SGA, and GLIM was 18.44%, 63.83%, and 75.89%, respectively. More than 80% of patients receiving chemotherapy had at least one digestive symptom, with taste changes accounting for the highest proportion (47.5%). Conclusions: The rate of malnutrition according to PG-SGA and GLIM, and the rate of digestive symptoms in patients receiving chemotherapy are pretty high. It is necessary to screen and assess the nutritional status of cancer patients receiving chemotherapy to have appropriate nutritional interventions, contributing to increasing treatment effectiveness.